"Profaning the sacred holidays with rites and gentilician ceremonies”. Confraternities, power and religiosities. Salta, 1750-1810 (Quinto Sol, 2018)
This work studies the characteristics of religious confraternities that congregated black people, natives and mestizos of the city of Salta, in the period between the second half of the 18th century and the beginning of the 19th. We analyze this, in order to approach religious manifestations of these social agents, their devotional preferences and their forms of associative integration. Also we focus on the relations between those social agents and the elite, the local civil and ecclesiastical authorities.
Keywords: confraternities; religious; interethnic relationships; blacks; indigenous and mestizos; community integration